VOLITIONAL STRATEGIES THROUGH METACOGNITIVE DEVELOPMENT IN FOSTERING READING MOTIVATION - Damaianti, Vismaia S. (Indonesian Journal of Applied Linguistics, 2017)
Student’s reading skill is deemed vitally important to attain high academic achievements. The results of the previous studies, however, show that Indonesian students' reading skill is still unsatisfying due to their low motivation. The purpose of this study is to address this problem of students’ motivation by examining the effectiveness of a volitional strategy through metacognitive development to students of Islamic Junior High School [Madrasah Tsanawiyah] in Indonesia. A quasi-experimental method with a factorial design is used in this research. Indicators for increasing students’ reading motivation come from Cambria and Guthrie (2010). Measures of increased motivation to read with the volitional strategy were done through metacognitive development which is based on self-monitoring and awareness of reading skills mastery. This study concludes that the volitional strategy through metacognitive development is proved effective in increasing students’ motivation for reading, students with both low and high reading skills. This has implications for the efforts to foster motivation for reading by intensively using the strategy for Madrasah Tsanawiyah education contexts.